2023
DOI: 10.1083/jcb.202206038
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin coats partially preassemble and subsequently bend during endocytosis

Abstract: Eukaryotic cells use clathrin-mediated endocytosis to take up a large range of extracellular cargo. During endocytosis, a clathrin coat forms on the plasma membrane, but it remains controversial when and how it is remodeled into a spherical vesicle. Here, we use 3D superresolution microscopy to determine the precise geometry of the clathrin coat at large numbers of endocytic sites. Through pseudo-temporal sorting, we determine the average trajectory of clathrin remodeling during endocytosis. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…Although 3DSIM can interpret the 3D hollow structure of CCPs, sparse deconvolution can make the hollow structure clearer. This is consistent with the physiological structure of CCPs, 32 and similar results were reported with 3D single-molecule localization microscopy 33 . Then, we use MRA deconvolution 34 for the processing of tubulin structure of the low signal-to-noise ratio in Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Although 3DSIM can interpret the 3D hollow structure of CCPs, sparse deconvolution can make the hollow structure clearer. This is consistent with the physiological structure of CCPs, 32 and similar results were reported with 3D single-molecule localization microscopy 33 . Then, we use MRA deconvolution 34 for the processing of tubulin structure of the low signal-to-noise ratio in Fig.…”
Section: Resultssupporting
confidence: 86%
“…This is consistent with the physiological structure of CCPs, 32 and similar results were reported with 3D single-molecule localization microscopy. 33 Then, we use MRA deconvolution 34 for the processing of tubulin structure of the low signal-to-noise ratio in Fig. 6(d).…”
Section: Computational 3d Deconvolutionmentioning
confidence: 99%
“…Class I oligomers have a diameter of ~75 nm that is smaller than the 100-200 nm diameter of clathrin pits and vesicles [23,24]. The Class II pits and vesicles have a blob area of 56,581 nm 2 that corresponds closely to the previously reported 54,000 nm 2 median surface area of clathrin pits imaged by SMLM [25]. Consistently, most hollow blobs identified by SMLM in Figure 1 are classified as Class II blobs.…”
Section: Discussionsupporting
confidence: 81%
“…Fig. 1) [25,26]. Euclidean distance analysis for 27 features (excluding volume and area), showed that Class I and Class II are highly similar between HeLa and Cos7 cells (Supp.…”
Section: Superresnet Smlm Network Analysis Detects Three Classes Of C...mentioning
confidence: 94%
“…By significantly extending the imaging throughput of fluorescence nanoscopy, PRIME-PAINT and the other recent, large-FOV modalities bring exciting new opportunities. Similar to cryo-EM single-particle analysis, which revolutionized structural biology, recent work has used nanoscopy data to infer dynamic protein complexes. , Large-scale nanoscopic image data sets will synergize with machine-learning-based image analysis tools such as WEKA and LocMoFit to significantly accelerate biomedical discovery. , Additionally, the ability to image FFPE sections at nanometer resolution across mm 2 FOVs (Figure and Figure S14) is an important step toward clinical applications, for which PRIME-PAINT and the likes represent a leap forward compared with prior attempts using electron microscopy (EM) or fluorescence nanoscopy with a small FOV. , …”
Section: Conclusion and Discussionmentioning
confidence: 99%